alrighty
remember some rules
[tex](ab)^c=(a^c)(b^c)[/tex]
and
[tex]x^{-m}=\frac{1}{x^m}[/tex]
and
[tex]x^0=1[/tex] for all real values of x
and
[tex](a^b)^c=a^{bc}[/tex]
and
[tex](\frac{a}{b})^c=\frac{a^c}{b^c}[/tex]
and
(a/b)/(c/d)=(ad)/(bc)
and
[tex](a^b)(a^c)=a^{b+c}[/tex]
and
[tex]\frac{a^m}{a^n}=a^{m-n}[/tex]
and don't forget pemdas
example: [tex]-x^m=-1(x^m)[/tex] but [tex](-x)^m=(-1)^m(x^m)[/tex]
so
4.
[tex](\frac{c^{-2}}{2})^{-2}=[/tex]
[tex]\frac{(c^{-2})^{-2}}{2^{-2}}=[/tex]
[tex]\frac{c^4}{\frac{1}{2^2}}=[/tex]
[tex]\frac{c^4}{\frac{1}{4}}=[/tex]
[tex]4c^4[/tex]
5.
[tex]\frac{(-a)^4bc^5}{-a^2b^{-3}c^0}=[/tex]
[tex]\frac{(-1)^4(a)^4bc^5}{-1(a^2)(\frac{1}{b^3}(1)}=[/tex]
[tex]\frac{(1)a^4bc^5}{\frac{(-1)(a^2)}{b^3}}=[/tex]
[tex]\frac{(a^4bc^5)b^3}{(-1)(a^2)}=[/tex]
[tex]\frac{-a^4b^4c^5}{a^2}=[/tex]
[tex]-a^2b^4c^5[/tex]